SWOT Analysis for Center of Technology Development and Industrial Collaboration in the Context of New Normal, Industry 4.0, and Society 5.0 - Damayanti, Retno Wulan; Setiadi, Haryono; Laksono, Pringgo Widyo; Triyono, Joko (BRILIANT: Jurnal Riset dan Konseptual, 2023)
Post-pandemic recovery in the new normal era is one of the challenges industries in 2022. This is in addition to the use of industry 4.0 and society 5.0, labeled as â€œtriple challengeâ€ by industries to determine their direction and business strategies. These factors become an opportunity for the Center of Technology Development and Industrial Collaboration or Pusat Kajian dan Pengembangan Teknologi dan Kolaborasi Industri (PKPTKI) to improve its management to support industries. Three steps were conducted to tackle those challenges. The first is identifying and mapping the industry partnerâ€™s challenges. The second is solution mapping to support them while facing the triple challenges, and lastly is formulating the solutions using SWOT analysis and developing a new roadmap for PKPTKI. The outputs are the partner challenges and knowledge mapping, SWOT analysis, and solution strategies with a planned improvement program.